TAKEOVERS AND THE DUTIES OF THE BOARD OF DIRECTORS: COMPARATIVE ASPECTS OF AMERICAN AND CANADIAN STANDARDS - Spector, Charles (Revue de droit de l'Université de Sherbrooke, 1989)
The most recent wave of corporate takeover activity has led to a myriad of takeover defence strategies. Adopted by the Board of Directors of target companies in reaction to a hostile takeover, their implementation, or failure to do so, has often led to protracted and costly litigation. While this phenomena is much more wide-spread in the United States, more and more Canadian companies are adopting similar takeover defences, the validity of which may ultimately end up being decided by the courts.In this article, the author examines the development of the standards currently applied by the courts in the United States to Board of Directors' responses to real or perceived takeover threats, to what extent these standards have similar application in Canada as well as the distinguishing features in Canadian corporate and takeover legislation which may account for notable differences.